Misuse of Islamic attributes in food products labelling and marketing in Malaysia - Osman, Suraiya; Jalil, Abdullaah; Ab Rahman, Suhaimi (UUM Press, 2020)
Various marketing techniques have been used to capture consumers' attention. Among them is using Islamic attributes. This practice has led to various negative impacts on the consumers and the Islamic dignity itself. The aim of this study is to identify the misuse of Islamic attributes in food products' labelling and to investigate the extent to which the use of Islamic attributes impacts the consumer and the Islamic dignity. In order to achieve the objectives, library research was carried out to collect relevant information. The materials also include online materials gathered from Google search engine. The materials are not only limited to the English language but also cover Malay language materials. The qualitative data from the library study was analyzed using the content analysis method. There are various types of misuse; first, is Quran-related such as Ruqyah, secondly Sunnah-related such as using the term Prophetic foods or the word Sunnah itself, thirdly by using Islamic icons. Fourthly, by using Islamic act of worships such as prostration in prayers and the fifth category is using an Islamic or Muslim's name. The last category is by using Jawi writings or Arabic terms in the label or trademark. These marketing techniques may lead to numerous effects, among others degrading the authority of Sunnah, health concern and exploiting Islam for commercial gain. The findings may act as a starting point to the policymakers in proposing some guidelines on the use of Islamic attributes in food product labeling and marketing in Malaysia.